Profesi di Era Youtube: Studi Kasus Jerome Polin dalam Menyampaikan Budaya Indonesia di Jepang - Nisya Aurora Afifa Afra Amanullah; Lutfiah Resti Hikmahita; Widya Indah Nurlaili; Suryo Ediyono; Suliyem (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This writing discusses the utilization of social media, focusing on the case study of Jerome Polin, a YouTuber who has successfully conveyed Indonesian culture in Japan with 10.5 million subscribers on his YouTube channel. In the context of globalization and the advancement of information technology, platforms like YouTube have become essential tools for sharing knowledge and culture. Jerome Polin, known for his content, not only entertains but also educates his audience about Indonesian culture, language, and daily life while studying in Japan, where he earned his bachelor's degree before returning to Indonesia as a famous YouTuber. This research analyzes Jerome's profession as a YouTube content creator, which he has turned into a source of income, the communication strategies he employs, the impact of his content on cultural understanding, and the interactions that take place between Japanese and Indonesian communities through social media. Using a qualitative approach, this study aims to provide insights into the role of influencers in introducing and promoting culture in the digital era, as well as the challenges faced in preserving cultural authenticity amidst the currents of globalization. The results show that Jerome Polin has successfully educated his audience while simultaneously strengthening intercultural relationships through innovative and creative approaches.